Deep song the life and work of Federico Garcia Lorca - Roberts, Stephen 1949-2022 (Reaktion Books, 2020)
Federico Garcia Lorca is Spain's most famous writer, and an icon of its culture. He is the author of a series of innovative works that changed the face of Spanish poetry and drama. In this new biography Stephen Roberts seeks out the roots of the man and his work in the places in which Lorca lived and died: the Granadan countryside where he spent his childhood; the Granada and Madrid of the 1910s, '20s and '30s where he was educated and first achieved success as a writer; and the mountains outside Granada where his body lies in an undiscovered grave. The book provides a full portrait of a complex and brilliant man, as well as giving new insights into the works that made his name
Keywords: García Lorca, Federico -- 1898-1936; García Lorca, Federico / 1898-1936 / Criticism and interpretation; García Lorca, Federico / 1898-1936; Criticism, interpretation, etc; Biografie